How organizational citizenship behaviors promote job performance: evidence from the aviation industry - Vuong, Bui Nhat; Hieu, Vo Thi; Lien, Le Thi Phuong; Huyen, Nguyen Thi Thanh (Business: Theory and Practice, 2024)
In the 21st century, the working environment is changing rapidly, and competition is fierce. In industries such as airlines, it is crucial to identify the factors that drive employee performance. This study aims to determine the elements of organizational citizenship behaviors (OCBs) that have an impact on work performance. A mixed research method was employed for the study, which collected survey data from 195 employees of ground service companies in Vietnam, including Saigon Ground Service Company (Sags), Vietnam Airport Ground Service Company (Viags), and Hanoi Ground Service Joint Stock Company (Hgs). The results revealed that five factors of OCBs affect job performance, ranked in descending order: (1) Voice-speaking up about concerns, (2) civic virtue, (3) conscientiousness, (4) courtesy, and (5) altruism. The study also proposed some implications for managers of ground service companies to enhance their employees’ job performance.